Agile construction for the electrical contractor - Daneshgari, Parviz (Sudbury, Mass. : Jones and Bartlett Publishers, 2010)
Agile Construction for the Electrical Contractor provides the tools and guidance needed to transform a traditional, reactive project management style to a new, proactive, profitable, and productive business management model - one that can quickly respond to changing industry needs and remain a profitable enterprise, even during the toughest of times. In this groundbreaking new book, Dr. Daneshgari applies proven managerial techniques from other industries to electrical construction through the introduction of Agile construction - a new scientifically-based tracking system based on jobsite dynamics and the bottom-line impact of the three sources of cost drivers: money, materials, and manpower. This practical and accessible guide to improving operating systems and efficiencies is a must-have for construction company owners, CEOs, project managers, and supervisors with its clear set of practical tools, processes and tips for improving productivity.
What is agile construction? -- Productivity and production -- Making it visible -- Making money -- Project planning -- Operational tools for agility -- Corporate tools for agile construction -- The supporting structure for agile companies -- Processes.
Includes bibliographical references (p. 225-227) and index.
Keywords: Electric contracting; Buildings -- Electric equipment; Construction industry -- Planning